Variations in physicochemical properties of airborne particles during a heavy haze-to-dust episode in Beijing - ZH Wang; W* Hu; Niu, H. Y.; Hu, W. W.; Y.S. Wu; LB Wu; LJ Ren; JJ Deng; Guo, S.; ZJ Wu; Zhang, D. Z.; Fu, P. Q.; et al. (SCIENCE OF THE TOTAL ENVIRONMENT, 2021)
The variations in physicochemical properties of airborne particles collected during a typical transition from haze to dust were investigated using single particle analysis with transmission and scanning electron microscopes combined with online measurement of chemical compositions of airborne particles in Beijing in February 2013. The transition was divided into three phases based on the weather condition. During haze pollution (Phase 1), gaseous and particle pollutants enhanced gradually. Results from single particle analysis showed that more coatings and more anthropogenic elements (e.g., S) appeared on the surface of fine and coarse particles, which was probably caused by efficient aqueous-phase reactions under high humidity (70%) condition. Phase 2 was dust intrusion episode. PM10 reached over 1000 mu g m(-3). Larger fractions of mineral particles and bare-like soot particles were observed in fine particles, while the fraction of secondary particles with coatings decreased. The proportion of black carbon in submicron particles also increased. Photochemical oxidation in gas phase likely dominated in secondary formation under high O-3 concentration. After the dust episode (Phase 3), secondary formation enhanced obviously. Soot aged quickly and had a larger mode of 0.45 mu m than the other phases. The size modes of airborne fine particles during Phases 1 and 3 were 0.35 mu m, which were a bit larger than that during Phase 2 (0.24 mu m). These results indicate that dust plumes accompanied with strong wind brought mineral particles in both fine and coarse modes and freshly emitted particles with smaller sizes, and swept away pre-presence air pollutants. This study could provide detailed information on the physicochemical properties of airborne particles during typical severe pollution processes in a short time. Such short-term change should be taken into account in order to more accurately assess the environmental, climatic and health-related effects of airborne particles.